Анализа корелације серума CCL3, TRACP-5b и склеростина са прогнозом пацијената са мултиплим миеломом: Серумски CCL3, TRACP-5b и склеростин код пацијената са мултиплим миеломом - Jiang, Cuimei; Sun, ManMan; Gao, Dashan; Zhang, Xiaoli; Pan, Jianan (Journal of Medical Biochemistry, 2025)
[Objective] To investigate the clinical use of Sclerostin, tartrate-resistant acid phosphatase 5b (TRACP-5b), and serum C-C motif chemokine ligand 3 (CCL3) levels in assessing the health and prognosis of patients with multiple myeloma.[Methods] 250 patients with multiple myeloma who visited the hospital between January 2023 and December 2024 were selected as the observation group, whereas 150 healthy individuals who were evaluated there during that time made up the control group. The levels of serum CCL3, TRACP-5b and Sclerostin in the observation group before and after treatment were compared, as were the levels of serum CCL3, TRACP-5b and Sclerostin. The levels of serum CCL3, TRACP-5b and Sclerostin in MM patients with different tumor stages and different degrees of bone destruction were compared, and the univariate and multivariate factors of death within one year in MM patients were analyzed. To compare the predictive efficacy of single and combined detection of serum CCL3, TRACP-5b and Sclerostin for death within one year in patients with multiple myeloma.[Results] The levels of serum CCL3, TRACP-5b and Sclerostin in the observation group before and after treatment were significantly greater than those in the control group, and the differences were statistically significant (P
Keywords: Тартрат-резистентна кисела фосфатаза 5б; Остеопероклин; Мултипла мијелома; Прогностичка корелација; Склеростин; Лиганд хемокина са мотивом Ц-Ц 3